2020
DOI: 10.1038/s41467-019-13957-x
|View full text |Cite
|
Sign up to set email alerts
|

Climate econometric models indicate solar geoengineering would reduce inter-country income inequality

Abstract: Exploring heterogeneity in the economic impacts of solar geoengineering is a fundamental step towards understanding the risk tradeoff associated with a geoengineering option. To evaluate impacts of solar geoengineering and greenhouse gas-driven climate change on equal terms, we apply macroeconomic impact models that have been widely applied to climate change impacts assessment. Combining historical evidence with climate simulations of mean annual temperature and precipitation, we project socioeconomic outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Bickel and Agrawal 66 suggested that even considering the probability and side effects of aborting geoengineering, SAI may still pass a cost-benefit test over a wide range of scenarios. Another approach has been to look at economic disparities under SAI compared with pure greenhouse gas forcing 67 , although no analysis was done for G4 or RCP4.5, disparities are greatly reduced with SAI which is hence beneficial to social stability. Although analyzing the cost-benefit of SAI as a whole, is fraught with difficulty because of unforeseen and presently unquantifiable damages from SAI, here we used the PAGE-ICE model to evaluate the global economic impacts of PCF, and for reference total economic damage as well.…”
Section: Resultsmentioning
confidence: 99%
“…Bickel and Agrawal 66 suggested that even considering the probability and side effects of aborting geoengineering, SAI may still pass a cost-benefit test over a wide range of scenarios. Another approach has been to look at economic disparities under SAI compared with pure greenhouse gas forcing 67 , although no analysis was done for G4 or RCP4.5, disparities are greatly reduced with SAI which is hence beneficial to social stability. Although analyzing the cost-benefit of SAI as a whole, is fraught with difficulty because of unforeseen and presently unquantifiable damages from SAI, here we used the PAGE-ICE model to evaluate the global economic impacts of PCF, and for reference total economic damage as well.…”
Section: Resultsmentioning
confidence: 99%
“…, 2015 ). For mitochondria, active mechanisms are also involved in positioning them near the nucleus in cells such as the oocyte ( Duan et al. , 2020) .…”
Section: Resultsmentioning
confidence: 99%
“…The effects of these technologies are also very uncertain, and deployment of sulfate particulates to provide temporary cooling may have adverse side effects on other sectors, regions, and actors. Some models find that SRM could reduce inter‐country income inequality by reducing the worse damages for vulnerable countries (Harding et al, 2020 ). By contrast, public discourse suggests that solar radiation management is perceived as more likely to create a world with an increased probability of geopolitical conflict and even present a challenge to democratic governance (Macnaghten & Szerszynski, 2013 ).…”
Section: Climate Policy Its Consequences and The Potential For Conflictmentioning
confidence: 99%